Multifractal analytical method and experimental study on crack evolution of dismantled RC hollow-slab beam. (June 2022) - Wang, Junfeng; Huang, Pingming; Yuan, Yangguang; Zhou, Guangli; Han, Wanshui
Abstract: Reinforced concrete is the earliest and most commonly used bridge construction material and there are a large number of RC bridges in service all over the world. Due to a long-time operation and external load, most concrete bridges suffer from various degrees of damage. The most common method used in the maintenance of these bridges is visual inspection, which is highly subjective, lacks quantitative means and provides little information about the mechanical properties of the structure. Therefore, this paper conducts a set of failure experiment of the reinforced concrete hollow slab beams based on multifractal theory, and then proposes a convenient damage detection method for reinforced concrete beam bridges based on crack distribution images. Firstly, this paper introduces the basis of multifractal theory and an example of its application to the cracking characteristics of concrete beam members. Then a set of failure experiment on demolished members of in-service reinforced concrete hollow slab bridges was conducted, and two high-precision industrial cameras were used to record the full process of crack development on the surface of the beams. Then the multifractal theory was used to quantitatively characterize the crack distribution characteristics of the beams during the load process. The function relationship between the fractal dimension and the bending moment and the main mechanical properties (mid-span deflection, maximum crack width) of the test beam was analyzed and the damage index based on fractal dimension is calculated. The results show that the multifractal theory performs appropriate in describing the crack distribution of the beam, the points on the multifractal spectrum continuously move to larger values as the bending moment increases, and the generalized fractal dimension values have similar conclusions. The functional correlation between main mechanical properties and the fractal dimension is strong. Based on the experiment results, the damage classification criteria for reinforced concrete bridges are proposed referred to the IAEA guidelines. Three damage classes and corresponding the range of values of fractal dimension ( FD ) and the damage index ( DI ) are given. These findings provide a useful tool for exploring the cracking performance and rapid detection of reinforced concrete bridges.